2017
DOI: 10.1002/14651858.cd004679.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial agents for preventing peritonitis in peritoneal dialysis patients

Abstract: In this update, we identified limited data from RCTs and quasi-RCTs which evaluated strategies to prevent peritonitis and exit-site/tunnel infections. This review demonstrates that pre/peri-operative intravenous vancomycin may reduce the risk of early peritonitis and that antifungal prophylaxis with oral nystatin or fluconazole reduces the risk of fungal peritonitis following an antibiotic course. However, no other antimicrobial interventions have proven efficacy. In particular, the use of nasal antibiotic to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 96 publications
2
29
0
6
Order By: Relevance
“…PD infection, including peritonitis, exit-site, and tunnel infections, was the highest ranked outcome overall, consistent with the frequency with which it is reported in trials (17,25). Patients felt they were constantly required to be extremely vigilant with their hygiene practices to minimize their risk of infection, which may jeopardize PD survival, cause pain, or require hospitalization.…”
Section: Discussionsupporting
confidence: 61%
“…PD infection, including peritonitis, exit-site, and tunnel infections, was the highest ranked outcome overall, consistent with the frequency with which it is reported in trials (17,25). Patients felt they were constantly required to be extremely vigilant with their hygiene practices to minimize their risk of infection, which may jeopardize PD survival, cause pain, or require hospitalization.…”
Section: Discussionsupporting
confidence: 61%
“…In this regard, it was disappointing to note that routine monitoring of PD infection rates was not universal across all participating PD facilities. Moreover, four randomized controlled trials (RCTs) and a systematic review have demonstrated the benefit of antibiotic prophylaxis at the time of PD catheter insertion (level 1A ISPD guideline) [9,[14][15][16][17]. While this practice was universally applied in all surveyed facilities in Canada and the UK, only 63% of facilities in the USA reported using prophylactic antibiotics at the time of PD catheter insertion and between 82% and 89% of facilities across other countries.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a significant proportion of fungal peritonitis episodes occur following a course of antibiotics [22]. Based on these observations coupled with the findings of two RCTs and a systematic review, the ISPD guidelines recommend antifungal prophylaxis with either oral nystatin or fluconazole when PD patients receive antibiotic courses (level 1B evidence) [9,14,23]. The particularly high uptake in ANZ may reflect ongoing continuous quality improvement initiatives, including a recent call to action in which the use of antifungal prophylaxis was strongly and locally endorsed [8,24,25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the exposure duration and timing of peritonitis defined by these studies differ, the role of prophylactic systemic antibiotic administration on preventing EOP remains uncertain. Furthermore a recently published Cochrane Systematic Review of this topic [25] references only a single study out of 39 which provides low quality evidence for intravenous vancomycin in reducing the risk of early peritonitis. Thus, it can be seen that EOP-specific preventative factors have been poorly elucidated.…”
Section: Preventative Strategiesmentioning
confidence: 99%